[Congressman Margarito Teves speaks on the Asian currency crisis] - Teves, Margarito (Animo Repository, 1998)
Congressman Margarito Teves gave a talk on, The Asian Currency Crisis before the GECODEV Class of Prof. Mila Beltran, Graduate School of Business.